Bistability of cell-matrix adhesions resulting from nonlinear receptor-ligand dynamics - Erdmann, Thorsten; Schwarz, Ulrich S. (Biophysical journal, 2009)
Bistability is a major mechanism for cellular decision making and usually results from positive feedback in biochemical control systems. Here we show theoretically that bistability between unbound and bound states of adhesion clusters results from positive feedback mediated by structural rather than biochemical processes, namely by receptor-ligand dissociation and association dynamics that depend nonlinearly on mechanical force and receptor-ligand separation. For small cell-matrix adhesions, we find rapid switching between unbound and bound states, which in the initial stages of adhesion allows the cell to explore its environment through many transient adhesions.
Gesehen am 10.07.2020